Efficacy of Trichoderma isolates against rot pathogens of small cardamom (Elettaria cardomomum Maton.) - K. DHANAPAL*, ANU ANIE MATHEWS and (Indian Phytopathology, 2016)
The antagonistic activities of sixty fungal isolates against rot pathogens of small cardamom viz., Phytophthora meadii and Pythium vexans were evaluated under in vitro. Three Trichoderma isolates viz., T17, T34 & T9 gave 73.33, 72 & 70.22 per cent inhibition respectively against P.meadii. Three Trichoderma isolates viz., T46, T30 & T56 gave maximum inhibition of 69.74, 69.3 & 69.3 per cent respectively against P. vexans. Studies on the mode of action of these superior isolates were undertaken under in vitro conditions. Percentage inhibition of P. meadii due to volatile and non-volatile metabolite production varied from 3.3-8.8% and 65.55-67.77% respectively. In case of Trichoderma isolates antagonistic to P. vexans, the inhibition percent due to volatile and non-volatile metabolite production varied from 1.1-3.3% and 65.55-67.77% respectively. Among the six superior isolates the production of IAA production varied from 0.444-1.628 Âµg/ml of broth.